Chemical Bonding in the Catalytic Platform Material Ga1‐xSnxPd2. Issue 12 (14th December 2022) - Ormeci, Alim; Gaudry, Emilie; Armbrüster, Marc; Grin, Yuri
Abstract: The underlying reasons for the catalytic activity of Ga1‐ x Sn x Pd2 (0 ≤ x ≤ 1) in the semi‐hydrogenation of acetylene are analyzed considering electronic structure and chemical bonding. Analysis of the chemical bonding shows pronounced charge transfer from the p elements to palladium and an unusual appearance of the Pd core basins at the surface of the QTAIM (quantum theory of atoms in molecules) atoms. The charge transfer supports the formation of the negatively charged palladium catalytic centers. Gallium‐only‐coordinated palladium atoms reveal a smaller effective charge in comparison with palladium species having tin in their coordination sphere. Within the empirical tight‐binding approach, different influence of the E ‐Pd distances on the calculation matrix for the energy eigenvalues and the electronic density of states (DOS) leads to an S‐like shape of the plot of the energy position of the 4 d band center of gravity versus substitution level x . The latter correlates strongly with the catalytic activity and with the varying charge transfer to palladium. The optimal value of negative palladium charge and the closest position of Pd d ‐states gravity center towards the Fermi level correlates well with the catalytically most active composition x . Combination of all features of the chemical bonding and electronic structure allows more insight into the intrinsic reasons for the catalytic activity variation in the platform material Ga1‐ x Sn x Pd2 (0 ≤ x ≤ 1). Abstract : Ga1‐ x Sn x Pd2 is a platform material in the semi‐hydrogenation of acetylene. Its catalytic activity is analyzed from the point of view of chemical bonding. Pronounced charge transfer from the p elements to palladium results in the formation of the negatively charged catalytic centers. Combination of all features of the chemical bonding and electronic structure yield the peak of catalytic activity at x ≈ 0.25.